2017
DOI: 10.15406/ijcam.2017.07.00263
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Hydroxyapatite from Bovine and Human Cortical Bone by Thermal Decomposition and Effect of Gamma Radiation: A Comparative Study

Abstract: Hydroxyapatite (HA) was extracted from bovine and human cortical bone by thermal decomposition process and was characterized using several analytical tools, including thermo-gravimetric analysis (TGA), X-ray diffraction analysis (XRD), X-ray fluorescence analysis (XRF), Flourier transformed infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Removal of organic matter from the bone was confirmed by TGA. XRD data confirmed that HA was the only crystalline phase when sintered at 950 °C. XRF analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(25 reference statements)
0
4
0
2
Order By: Relevance
“…The FTIR spectrum of synthesized HAp is shown in Figure 3 where peaks centred at 555.50, 594.08, and 1018.14 cm −1 were recorded. The strong and sharp peak at 1018.41 cm −1 is due to the asymmetrical stretching of the phosphate group, while two relatively sharp peaks at 555.50 and 594.08 cm −1 are due to the symmetrical stretching of the phosphate group which gives authenticated information about the vibrational origin of the phosphate to indicate the production of HAp [25, 36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR spectrum of synthesized HAp is shown in Figure 3 where peaks centred at 555.50, 594.08, and 1018.14 cm −1 were recorded. The strong and sharp peak at 1018.41 cm −1 is due to the asymmetrical stretching of the phosphate group, while two relatively sharp peaks at 555.50 and 594.08 cm −1 are due to the symmetrical stretching of the phosphate group which gives authenticated information about the vibrational origin of the phosphate to indicate the production of HAp [25, 36].…”
Section: Resultsmentioning
confidence: 99%
“…The bones were then dried, ground using a rotary mill, and sieved using a 450-μm sieve. Finally, the obtained powder was calcined at two different temperatures, first at 600 • C for 3 h and then at 900 • C for 3 h to ensure removal of the organic constituents and the carbonate apatite hence obtain a white powder of HAp [25,26].…”
Section: Synthesis Of Hydroxyapatite (Hap) From Chicken Bonesmentioning
confidence: 99%
“…HAp adalah salah satu bio keramik yang memiliki sifat biokompatibel, biodegradable dan tidak beracun (Siswoyo et al, 2020). HAp dapat diekstraksi dari berbagai tulang seperti tulang sapi (Asaduzzaman, 2017), kakap putih (Pal et al, 2017) dan tulang ikan tenggiri (Anggresani et al, 2019).…”
Section: Iunclassified
“…Dengan metode yang sama dilakukan oleh (Indrani et al, 2017) dihasilkan kristalinitas HAp sebesar 65% pada suhu 900°C dan terbukti memiliki struktur kristal heksagonal. (Asaduzzaman, 2017) juga berhasil melakukan ekstraksi HAp dari tulang kortikal sapi dan manusia pada suhu 950 °C-1250 °C menghasilkan derajat kristalinitas sebesar 98,51%-98,92%.…”
Section: Iunclassified
“…There was no information provided about the breed and the exact age of the obtained goose bones from the local slaughterhouse. These goose attributes can influence the hydroxyapatite composition of calcified tissues [25]. A similar study by Bahrololoom et al successfully demonstrated the detection of numerous elements in cortical bone from cattle [26].…”
Section: Xrf Analysismentioning
confidence: 99%